Potential of Herbariomics for Studying Repetitive DNA in Angiosperms - Dodsworth, Steven; Guignard, Maïté S.; Christenhusz, Maarten J. M.; Cowan, Robyn S.; Knapp, Sandra; Maurin, Olivier; Struebig, Monika; Leitch, Andrew R.; Chase, Mark W.; Forest, Félix (Frontiers in Ecology and Evolution, 2018)
Repetitive DNA has an important role in angiosperm genomes and is relevant to our understanding of genome size variation, polyploidisation and genome dynamics more broadly. Much recent work has harnessed the power of high-throughput sequencing (HTS) technologies to advance the study of repetitive DNA in flowering plants. Herbarium collections provide a useful historical perspective on genome diversity through time, but their value for the study of repetitive DNA has not yet been explored. We propose that herbarium DNA may prove as useful for studies of repetitive DNA content as it has for reconstructed organellar genomes and low-copy nuclear sequence data. Here we present a case study in the tobacco genus (Nicotiana; Solanaceae), showing that herbarium specimens can provide accurate estimates of the repetitive content of angiosperm genomes by direct comparison with recently-collected material. We show a strong correlation between the abundance of repeat clusters, e.g. different types of transposable elements and satellite DNA, in herbarium collections versus recent material for four sets of Nicotiana taxa. These results suggest that herbarium specimen genome sequencing (herbariomics) holds promise for both repeat discovery and analyses that aim to investigate the role of repetitive DNAs in genomic evolution, particularly genome size evolution and/or contributions of repeats to the regulation of gene space.